Prognostic factors associated with healing of venous leg ulcers: a multicentre, prospective, cohort study. (31st October 2013) - Chaby, G.; Senet, P.; Ganry, O.; Caudron, A.; Thuillier, D.; Debure, C.; Meaume, S.; Truchetet, F.; Combemale, P.; Skowron, F.; Joly, P.; Lok, C.; et al.
Abstract : What's already known about this topic? Despite advances in venous leg ulcer (VLU) management, the time to ulcer healing generally remains long. Some prognostic markers of healing have been evaluated, mostly in retrospective studies. What does this study add? In this prospective, multicentre, cohort study, complete healing of long‐standing, large VLUs at 6 months was independently associated with ablation of the incompetent superficial vein and percentage of wound area reduction after the first 4 weeks of treatment. Summary: Background: Some prognostic markers of venous leg ulcer (VLU) healing have been evaluated, mostly in retrospective studies. Objectives: To identify which clinical characteristics, among those known as possible prognostic factors of VLU healing, and which VLU‐associated sociodemographic and psychological factors, are associated with complete healing at week 24 (W24). Methods: A prospective, multicentre, cohort study was conducted in 22 French dermatology departments between September 2003 and December 2007. The end point was comparison between healed and nonhealed VLUs at W24, for patient clinical and biological characteristics; psychological, cognitive and social assessments; affected leg inclusion characteristics; venous insufficiency treatment and percentage of initial wound area reduction during follow‐up. Results: In total, 104 VLUs in 104 patients were included; 94 were analysed. The mean VLU area and duration were 36·8 ± 55·5 cm 2 and 24·8 ± 45·7 months, respectively. At W24, 41/94 VLUs were healed. Univariate analysis significantly associated complete healing with superficial venous surgery ( P  =   0·001), adherence to compression therapy at W4 ( P  =   0·03) and W24 ( P  =   0·01), ankle‐joint ankylosis ( P  =   0·01) and mean percentage of VLU area reduction at W4 ( P  =   0·04). Multivariate analysis retained superficial venous surgery during follow‐up [odds ratio (OR) 8·4, 95% confidence interval (CI) 1·9–48·2] and percentage reduction of the VLU area at W4 (OR 1·6, 95% CI 1·0–2·14) as being independently associated with healing. Conclusions: These results indicate that complete healing of long‐standing, large VLUs is independently associated with ablation of the incompetent superficial vein and percentage of wound area reduction after the first 4 weeks of treatment.